Negation of Fauna Sustainability and the Extinction of the Rampogan Macan Tradition in Java, 1880s to 1900s - Siska Nurazizah Lestari; Nugraha Nugraha; Indra Fibiona (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
From the 1880s to the early 1900s on the island of Java, there was a unique tradition, namely the Rampogan Macan/Rampok Macan tradition. Javanese people community elite carried out this tradition until the early nineteenth century, but for reasons of animal preservation, the Dutch then banned the event. Questions in this research: How was the Rampogan Macan Tradition event until it was declared prohibited by the colonial government? This study uses historical methods. The study results show that the Rampogan Macan tradition as a conflict tradition in Java is a development of the Rampogan Macan tradition in Surakarta. Along with the decreasing population of the Javanese tiger, this tradition was later discontinued for reasons of preserving the fauna, but the big event was held in Java. The main reason the elites held tiger rampok was none other than the prestige they had won.